Two Fourteenth-Century Islamic Philosophers: Ibn Mubārakshāh al-Bukhārī and Mullāzāde al-Kharziyānī - El-Rouayheb, Khaled (Oriens, 2020)
Abstract Two handbooks were central to the study of philosophy in the Islamic world in the period from the thirteenth to the nineteenth centuries: the introductory Hidāyat al-ḥikma by Athīr al-Dīn al-Abharī (d. 663/1265), and the more advanced Ḥikmat al-ʿayn by Abharī’s student Najm al-Dīn al-Kātibī al-Qazwīnī (d. 675/1276). Two fourteenth-century scholars play an important part in the early commentary tradition on these two works: Ibn Mubārakshāh al-Bukhārī who wrote what was to become the standard commentary on Kātibī’s Ḥikmat al-ʿayn , and Mullāzāde al-Kharziyānī, who wrote an influential commentary on Abharī’s Hidāyat al-ḥikma . Despite the impact of the two commentaries, biographical information on their authors is sparse, and what has been written often confuses them with other figures. The present article attempts to review the available evidence, and to offer more secure identifications of the two commentators.